THE EFFECT OF DIFFERENT TYPES OF MEAT ON THE ACCEPTANCE OF SKIPJACK TUNA (Katsuwonus pelamis) - Nababan, Susy Suelestari; ', Sukirno; ', Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Research on the effect of the types of skipjack tuna (white and red meat) as raw material of skipjack abon was conducted in May 2017. This study aims to determine the best type of meat to the acceptance of shredad skipjack tuna. The method used is the experimental method of separating the two types of meat (white and red) each used as raw material abon tuna. The experimental design used was Completely Randomized Design (RAL) of one factor consisting of three levels ie D1 (White Meat 500 g), D2 (Red Meat 500 g) and D3 (White Meat and Red Meat 500 g). Replicated 3 times, in number of research nine units. It was found that the white meat weel accepted by the funnelished was 95%. From each treatment, the values of color, odor, texture, and taste were 97.5%, 92.5%, 91.25%, and 98.75%, respectively. Characteristic of yellowish brown color, typical smell of fish abon feels and seasoning tastes, smooth texture, dry and soft, the flavor of fish tasty and very tasty. The best proximate level was the D2 from the aquet water content, ash content, protein content, fat content respectively 10,90%, 5,98%, 21,12%, 28,60%. Keywords: Skipjack tuna, Abon